Evaluation of Lipid Profile and Hematological Changes Among Pregnant Women with Hypertension in Sebha City, Southern Libya - Abdullah, Fatmah; Wijdan O Alshami; Naji M Laji (Sebha University Conference Proceedings, 2025)
Disorders of pregnancy-induced hypertensive are a major health problem worldwide and they are one of the leading causes of maternal and perinatal morbidity and mortality. This study aimed to assess alterations in lipid profiles and hematological parameters among pregnant women with gestational hypertension. Conducted at Sebha Medical Center, 105 participants was divided into three groups: normotensive pregnant women, pregnant women with hypertension, and those with gestational hypertension. Complete blood count (CBC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol (TC), and triglycerides (TG) were determined. Findings revealed that TG and LDL levels were elevated in the gestational hypertension group compared to the normotensive group. Moreover, HDL levels were significantly reduced in both the hypertensive and gestational hypertension groups. However, no significant changes in TC levels were observed among study groups. The results also showed changes in the values of mean cell volume (MCV), platelet count (Plt), and lymphocyte count (Lym) among all groups of study. Conversely, there were no significant differences in hemoglobin (Hb), red blood cells (RBC), mean cell hemoglobin (MCH), mean cell hemoglobin concentration (MCHC), white blood cells (WBC), packed cell volume (PCV), and neutrophil count (NEUT). In conclusion, these results suggest that both gestational hypertension and chronic hypertension during pregnancy are associated with dyslipidemia, which was remarkable by increased TG and LDL levels and decreased HDL. Additionally, some hematological alterations may accompanying with hypertensive disorders in pregnancy